Relationship between Liquidity Risk and Net Interest Margin of Conventional Banks in Bangladesh - Chowdhury, A. N. M. Minhajul Haque; Siddiqua, Ayesha; Chowdhury, Abu Sayed Md. Mahmudul Haque (Asian Business Review, 2016)
Net interest margin (NIM) of a bank depends on several firm-specific factors. The aim of the study was to determine the effect of liquidity risk on the profitability indicating variable NIM of the conventional banks in Bangladesh. Seven banks were analyzed using the annual reports of the banks for the period of 2011 to 2015. Researchers applied descriptive statistics, correlation, and regression analysis to find out the results. The findings of the study provided evidence that cash to asset (CA) ratio had a negative relationship with NIM but a loan to asset (LA) ratio had a positive effect on the NIM. There was also a significant positive relationship between NIM and loan to deposit (LD) ratio. From the regression analysis it was clear that the LD, CA, and LA were able to explain the changes of NIM of the banks. JEL Classifications: G 21